Is multiple session of intralesional bleomycin mandatory for complete resolution of macrocystic lymphatic malformation? - Vijai Datta Upadhyaya; Ankur Bhatnagar; Basant Kumar; Zafar Neyaz; J. S. Kishore; Eti Sthapak (Indian Journal of Plastic Surgery)
Background: Intralesional bleomycin scelro-therapy has become a favored line of treatment for macrocystic lymphatic malformations. However the need for multiple sessions is a drawback associated with this treatment modality. Our aim is to document whether multiple session of intra-lesional sclero-therapy is necessary for complete resolution of cystic lymphatic malformation. Method: Intralesional bleomycin under Ultrasound guidance was used for macrocystic lymphangioma at concentration of 3mg/ml but not exceeding the total dose (1mg/kg) body weight for single session or cumulative dose of 5mg/kg. In all cases intralesional sclerosant (ILS) was installed under proper aseptic precaution in operation theatre in general anesthesia or sedation depending on the site or size of lesion and age of the patient. Age of patients at the time of enrolment in study ranged from 3 months to 18 years. Clinical examination was the main stay of diagnosis which was supplemented by USG and/or computed tomography. Compression of the lesion site was done for few hours wherever it was possible after the ILS session. Result: A total of 21 patients included in our study. The age ranged from 3 months to 18 years. Male to female ratio was 8:13. The most common site of involvement was neck and axilla followed by anterior chest wall and nape of the neck. Complete resolution after single session was observed in 90.5% cases where as surgery was required in 9.5% case. Major complication was observed in one patient, who had intralesional bleeding which was managed conservatively. Transient pain and fever was observed in 23.8% of cases. Only two patient required surgical intervention where one had persistent subcutaneous fibrotic nodule and other one did not respond to ILS. Conclusion: Intralesional bleomycin is an effective treatment for macrocystic lesion, and complete resolution may be achieved by single session of ILS if proper principle are followed.